PENGARUH KULTUR TUNGGAL FUNGI MIKORIZA ARBUSKULA (FMA) TERHADAP PERTUMBUHAN TANAMAN PADA MEDIA BEKAS TAMBANG PASIR - Fauziah, Fika; Karyaningsih, Ika; Nurlaila, Ai (Wana Raksa, 2024)
The rehabilitation strategy for improving the fertility of ex-sand mining soil must be able to improve the ecological conditions of the damaged mining environment, so that its growth can then be symbiotic with indigenous AMF. The types of plants that have the potential to be developed and are quite well known to the public are the types of plants that have economic value for the community and also have ecological value, where these plants are cut down so that they can improve the ecosystem condition of the former sand mining land in the area. Types of MPTS that might be developed include jackfruit, soursop and sugar apple plants. The type of plant chosen is aimed at land reclamation and also has a social and economic function for the community. This research was conducted in April - August 2023 at the Green House and Silviculture Laboratory, Faculty of Forestry and Environment, Kuningan University. In this study there were 2 variables, namely the independent variable which included the mycorrhizal genus and plant type, while the dependent variable included plant stem height, plant root length, plant root volume, number of spores on the plant. This research uses a Factorial Completely Randomized Design (CRD) data analysis method using SPSS software with two-way Analysis of Variance (ANOVA) at an error rate of 5%. The results showed that the use of the mycorrhizal genus independently had a very significant influence on the number of spores, but did not have a significant influence on the growth of stem height and root length. The use of plant species independently had a very significant influence on the growth of stem height, root length and root volume, but did not have a significant influence on the number of spores. Meanwhile, the interaction between the mycorrhizal genus and plant type had a very significant influence on root volume and did not have a significant influence on the growth of stem height, root length and number of spores.